Prototipe Alat Pendeteksi Banjir Berbasis Mikrokontroler dengan Fuzzy Tsukamoto - Alwi Andika Panggabean; M Fakhriza (Forum Kerjasama Pendidikan Tinggi, 2026)
Floods are among the most frequent natural disasters in Indonesia, causing significant material losses and casualties. Therefore, an early warning system capable of detecting flood potential quickly and accurately is required. This study aims to design and implement a flood detection prototype based on the ESP32 microcontroller using the Tsukamoto fuzzy logic method. The system employs an HC-SR04 ultrasonic sensor to measure water levels and an FC-37 rain sensor to detect rainfall intensity. Data collected from both sensors are processed using the Tsukamoto fuzzy logic approach through fuzzification, inference, and defuzzification stages to determine flood risk status categorized as safe, alert, and danger. The decision results are displayed through LED indicators and a buzzer, while real-time notifications are sent via the Telegram application using the ESP32 Wi-Fi connectivity. The testing results demonstrate that the system successfully classifies flood conditions according to the predefined fuzzy rules and automatically delivers notifications to users. The implementation of the Tsukamoto fuzzy logic method enhances decision-making capabilities in handling uncertain environmental conditions. Therefore, the developed prototype can serve as an effective, simple, and practical flood early warning system for flood-prone areas.